Comparison of external stents and DJ stents techniques for pediatric pyeloplasty: A systematic review and meta-analysis - Meng, Chunyang; Gan, Lijian; Li, Kangsen; Peng, Lei; Li, Jinze; Yang, Junbao; Li, Yunxiang (Frontiers in Pediatrics, 2022)
Objective: To evaluate and compare the efficacy and safety between an external stent and a double J stent for pediatric Pyeloplasty. Methods: Through a systematical search of multiple scientific databases in Aug 2021, we performed a systematic review and meta-analysis of the primary outcomes of interest according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), whose protocol was registered with PROSPERO(CRD42021274087). Results: Eleven studies involving 1758 patients were included. No significant differences were observed in operative time (MD:2.26; 95% CI -9.62 to 14.14; P= 0.79), operative success rate (OR:1.10; 95% CI 0.57 to 2.10; P= 0.780), length of hospital stay (MD: 0.65; 95% CI -0.04 to 1.34; P= 0.063), or complications (OR:0.87; 95%CI 0.48 to 1.56; P= 0.630) between external stents and double J stents in pediatric pyeloplasty. According to the subgroup analysis, we found the external stent group had a shorter operative time than the double J stent group in terms of robot-assisted laparoscopic pyeloplasty (MD: -17.13; 95% CI -32.8 to -1.45; P= 0.032). Conclusions: There were no significant differences in operative time, operative success rate, length of hospital stay, or complications between external stents and double J stents in pediatric pyeloplasty. The external stented procedure seemed to have less operative time when using robot-assisted laparoscopic pyeloplasty. However, due to the limitations of our analysis, more studies are still required to support our conclusion.